Reflections on Naming and Necessity. Issue 2 (12th December 2021) - Devitt, Michael
Abstract: This paper celebrates the fortieth anniversary of Naming and Necessity by gathering together some reflections I have made on that work over the years. The paper focuses on aspects of the book that I think have been misunderstood, overlooked, mistakenly rejected, or simply merit more emphasis. The paper starts with the philosophy of language, first discussing Kripke's most powerful argument against description theories of reference: the "ignorance and error" argument. It then considers Kripke's causal‐historical "better picture"; his discussion of rigidity; and finally, "direct reference" an implausible doctrine that has been wrongly attributed to Kripke. The rest of the paper is concerned with essentialist doctrines that Kripke has urged about biological kinds, chemical kinds, and individuals. These doctrines have been trenchantly criticized by some philosophers of science. I think that the relevant sciences support Kripke and do not support the critics.